2020
DOI: 10.26717/bjstr.2020.25.004218
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Withanolides

Abstract: Withanolides is a class of active compounds widely found in Solanaceae plants. In traditional applications, it has a long history and a wide range of functions. With the progress of drug structure and pharmacological research, more and more reports point to its excellent anticancer effect. Solanaceae is widely distributed, providing a large number of sources for the structure and pharmacological research of its natural products. At the same time, in the light of market demand, the circulation of such medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In W. somnifera, withanolides are mainly found in leaves and roots ranging from 0.001 to 0.5 % of dry weights. Modern research has shown that a number of withanolides have promising pharmacological properties for the treatment of inflammation-associated chronic diseases including cancer, arthritis, autoimmune and neurodegenerative diseases (White et al 2016; Wang 2020). So far, over 40 withanolides have been reported from this plant of which withaferin A and withanolide D have been reported to be the main active compounds contributing to the medicinal properties of Ashwagandha (Dhar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In W. somnifera, withanolides are mainly found in leaves and roots ranging from 0.001 to 0.5 % of dry weights. Modern research has shown that a number of withanolides have promising pharmacological properties for the treatment of inflammation-associated chronic diseases including cancer, arthritis, autoimmune and neurodegenerative diseases (White et al 2016; Wang 2020). So far, over 40 withanolides have been reported from this plant of which withaferin A and withanolide D have been reported to be the main active compounds contributing to the medicinal properties of Ashwagandha (Dhar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of these compounds varies based on the type of tissue and stage of the plant, ranging from 0.001 to 0.5% of the dry weights (Tetali et al, 2021). Modern research has shown that a number of withanolides have promising pharmacological properties for the treatment of inflammation‐associated chronic diseases, including cancer, arthritis, autoimmune and neurodegenerative diseases (White et al, 2016; Wang, 2020). Though several withanolides are found in this plant, only withaferin A and withanolide D have been extensively studied for their medicinal properties (Dhar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%